ROLE AND FUNCTIONS OF ACADEMIC AND TEACHING STAFF IN ACCOMPLISHING THE TASKS OF ENVIRONMENTAL EDUCATION - Demeshkant, Natalia A.; Pabat, Viktoria V. (Educological discourse, 2016)
The article analyzes the content of the main program documents of international environmental forums in the period from the first International Conference on Environmental Education in 1977, Tbilisi to the eighth World Environmental Education Congress in 2015, Gothenburg. The strategic directions of development of environmental education according to the international community are indicated. Changing objectives from environmental education to education for sustainable development are offered. The article highlights poverty reductions, promotion of a green economy, the formation of national educational policy as the modern trends of environmental education.